What is (5 -(sqrt)2) (3 + sqrt 2)?

1 Answer
Sep 18, 2015

13+2sqrt2

Explanation:

First we must expand the equation of (5 -sqrt 2) (3 + sqrt 2). And we will get the equation be like;

(5 -sqrt 2) (3 + sqrt 2)

=5(3)+5(sqrt2)-3(sqrt2)-sqrt2(sqrt2)

Note that for sqrt2(sqrt2), we can calculate it by;

=sqrt2xxsqrt2= (2)^(1/2)xx(2)^(1/2)= 2^(1/2+1/2)= 2^1 =2

And we will get;

=15+5sqrt2-3sqrt2-2

5sqrt2 can subtract 3sqrt2 since it has the same base, which is sqrt2. Calculate all of it and we will get;

=13+2sqrt2